Association between commuting to school and physical fitness related to motor performance in schoolchildren - Pires, Aillyn Lyanna (2017)
Background and objectives: Physical fitness and motor performance are important cardiometabolic risk predictors. The aim of this cross-sectional study was check for associations between commuting to school in school, physical fitness related to motor performance. Methods: The sample consists of 751 children and adolescents, 349 females and 312 males, aged between 7 and 17 years living in the city of Santa Cruz do Sul, state of Rio Grande do Sul. For the evaluation of commuting to school a questionnaire was used. For the assessment of physical fitness, the agility, speed, horizontal jump and medicine ball test were performed. Results: Most of the boys (81.4%) and girls (84.1%) moves in sedentary way to school, and girls moving actively to school have better strength levels of upper limbs (p = 0.023) and speed (p = 0.003). No significant result was observed in boys relating physical fitness and commuting to school. Conclusion: It was found that active commuting girls have shown better results in physical fitness tests. KEYWORDS: Adolescent. Physical Fitness. Child. Motor Skills. Schools.